State of the Art in Parent-Delivered Pain-Relieving Interventions in Neonatal Care: A Scoping Review - Ullsten, Alexandra; Andreasson, Matilda; Eriksson, Mats (Frontiers in Pediatrics, 2021)
Introduction: Parents’ active involvement during painful procedures is considered a critical first step in improving neonatal pain practices. Of the non-pharmacological approaches in use, the biopsychosocial perspective supports parent-delivered interventions, in which parents themselves mediate pain relief, consistent with modern family-integrated care. This scoping review synthesizes the available research to provide an overview of the state of the art in parent-delivered pain-relieving interventions. Methods: A scoping review was performed to achieve a broad understanding of the current level of evidence and uptake of parent-driven pain- and stress-relieving interventions in neonatal care. Results: There is strong evidence for the efficacy of skin-to-skin contact and breastfeeding, preferably in combination. These parent-delivered interventions are safe, valid, and ready for prompt introduction in infants’ pain care globally. Research into parents’ motivations for, and experiences of, alleviating infant pain is scarce. More research on combined parent-delivered pain alleviation, including relationship-based interventions such as the parent’s musical presence, is needed to advance infant pain care. Guidelines need to be updated to include infant pain management, parent-delivered interventions, and the synergistic effects of combining these interventions and to address parent involvement in low-income and low-tech settings. Conclusions: A knowledge-to-practice gap currently remains in parent-delivered pain management for infants’ procedure-related pain. This scoping review highlights the many advantages of involving parents in pain management for the benefit not only of the infant and parent, but also of health care.